Perspektif Fiqh Siyasah terhadap Peran Dinas Sosial dalam Menangani Anak Jalanan di Kota Bandar Lampung - S, Kartika; Yolanda, Deni; Maraliza, Helma (Universitas Islam Negeri Raden Intan Lampung, 2021)
The existence of street children, homeless people and beggars using the road is not in accordance with the function of the road because it can interfere with safety, security and smooth traffic. Along with the implementation of regional autonomy policies, the regions must play an active role in carrying out efforts to handle these social problems through the role of the Social Service. The research method using field research is carried out by reviewing data sourced from the research location or field. Based on its nature, this research is a descriptive study, namely a study to describe certain phenomena or symptoms. Based on the results of the research, the role of the Bandar Lampung City Social Service is in accordance with the principles of Islamic law, namely having a role to handle street children, namely by controlling the streets, which is handed over to the POL-PP for later coaching at the Bandar Lampung City Social Service. deemed disturbing, they will be arrested and brought to the Social Service and summoned by the family, a report is made in the form of an agreement as an effort to prevent it from happening again. During the coaching street children are given spiritual showers, as well as training and useful teachings. So that later street children will get provisions for a more decent life and can work with the skills that have been given.